(untitled) - Creswell, John W. (Upper Saddle River, N.J, 2005)
The first introduction to educational research text to offer a truly balanced, inclusive, and integrated overview of the field as it currently stands. The book's coverage is unique not only in its balanced coverage of quantitative, qualitative, and mixed method research designs but also in its examination of the research process from both quantitative and qualitative perspectives.
Keywords: Education; Methodology,Research